Students Attitudes Towards the Study-teaching of Research primary teacher line high class end of school year vacation period system 11+1+2 year 1, Khangkhay Teacher Training College in Academic Year 2022-2023: https://doi.org/10.69692/SUJMRD0901348 - MALAYSAN, Pany (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research is about research "Students Attitudes Towards the Study-teaching of Research primary teacher line high class end of school year vacation period system 11+1+2 year 1, Khangkhay Teacher Training College in Academic Year 2022-2023". The aim is 1) To study the attitude of students towards teaching-learning of Research primary teacher line high class end of school year vacation period system 11+1+2 year 1 in Khangkhay Teacher Training College in Academic Year 2022-2023 and 2) To study the problem of obstacles and improvement guidelines study-teaching of Research in Khangkhay Teacher Training College. This study uses quantitative data, The sample group used in the study wass tudents primary teacher line high class end of school year vacation period system 11+1+2 year 1 which has a total 30 People, the instrument used in the research is a questionnaire, Statistics used: Average value and Standard exchange rate The data analysis results are expressed as follows: The results of the analysis Students Attitudes Towards the Study-teaching of Research primary teacher line high class end of school year vacation period Academic Year 2022-2023 overall all aspects are moderate which has an overall average value equal to ( =3.41), The standard deviation is equal to (SD=0.03). When separated into each side, it is expressed as: Overall course content and sort by item is at several levels which has an average value, The standard deviation is equal to ( =3.57; SD=0.02). The organization of teaching-learning activities as a whole and sort by item is at several levels which has an average value, The standard deviation is equal to ( =3.55; SD=0.03). The use of teaching materials as a whole and and sort by item is at a moderate level value, which has an average value, The standard deviation is equal to ( =3.38; SD=0.03). Overall environment and sort by item is at a moderate level which has an average value, The standard deviation is equal to ( =2.96; SD=0.03). Overall measure ment and evaluation and sort by item is at a moderate level which has an average value, The standard deviation is equal to ( =3.61; SD=0.03).